A Cross-sectional study to identify the factors contributing to low uptake of 1st ANC services among pregnant mothers in first trimester at Kamira Health Centre III, Luweero District. - Mwesigwa , Edward (Student's Journal of Health Research Africa, 2022)
Background: A study was carried out to identify the factors contributing to low uptake of 1st ANC services among pregnant mothers during the first trimester at Kamira Health Centre III, Luweero District. The study design was descriptive and cross-sectional and it employed both quantitative and qualitative data collection methods. A sample of 60 respondents was selected using a purposive sampling procedure and an interview guide was used to collect data. Results: Socio-economic factors contributing to low uptake of 1st ANC services among pregnant mothers during the first trimester as 36 (60%) reported 4 – 6 months as the age at which they were supposed to start attending ANC services, 40 (66.7%) started attending ANC between 4 – 6 months and the major reasons were lack of awareness/knowledge 24 (40%) and lack of support 16 (26.7%). 40 (66.7%) reported that the income was not enough to enable access to ANC services as 24 (40%) resided 4 – 5 km away and 24 (40%) spent between 5,000 – 10,000shs on transport to the health facility. Health facility factors contributed to low uptake of 1st ANC services among pregnant mothers during the first trimester as 40 (67%) reported that Kamira Health Centre III was understaffed, and 20 (50%) had the inadequate infrastructure to handle large numbers of mothers. 40 (67%) reported that health workers had negative attitudes during the provision of ANC services to mothers 24 (40%) mentioned that they were rude and unwelcoming and 16 (26.7%) mentioned that health workers had poor customer care skills. Conclusion: Respondents faced various socio-economic, cultural, and health facility factors which contributed to low uptake of 1st ANC services among pregnant mothers during the first trimester. Recommendations: Including improving efficiency and reducing waiting time, improving customer care, more support, and health education about ANC among others.